The "Turnkey School" project model for teacher team training - Nechaev, Vladimir; Avdeeva, Irina (Jurnal Cakrawala Pendidikan, 2023)
This study aims to present a new model of professional training for teachers in educational institutions within the framework of the "Turnkey School" project within the Master of Education degree program at the Humanitarian and Pedagogical Institute of Sevastopol State University (SevSU). This study used a controlled research design method to validate the team concept through a proposed model based on the socio-constructivist and contextual paradigms in education. The model involves training in a master's program as part of team building for a new educational institution in which cohort groups are formed based on the specific needs of assigned schools, which are then evaluated by an independent community of experts, as well as with the writing of a final thesis as a result of cohort team collaboration. This study confirms that the cohort group formed through this model shows a better level of maturity and functioning than randomly assigned teachers. These findings support the effectiveness of a Master of Education degree in improving the training and performance of future teachers. This model emphasizes not only the creation of updated educational products but also the self-implementation of those products, which contributes to the overall improvement of educational institutions.